2020
DOI: 10.1371/journal.pone.0231590
|View full text |Cite
|
Sign up to set email alerts
|

Daily versus stat vitamin D supplementation during pregnancy; A prospective cohort study

Abstract: Background Despite favorable climatic conditions, vitamin D deficiency (VDD) is widespread in Pakistan. Current study was aimed to evaluate the prevalence of VDD in Pakistani pregnant women and effectiveness of various regimen of Vitamin D supplementation. Methodology This hospital-based prospective cohort study included pregnant women at 12 th to 24 th weeks of gestation attending Gynae clinic from October 2018 to April 2019. Patients were classified into control and treatment groups (Groups: G 1 , G 2 and G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
7
0
2
Order By: Relevance
“…In 2011, the Endocrine Society recommended 1000-4000 IU/day (up to 10.000 IU/day particularly for obese individuals) vitamin D supplementation to reach serum 25-OH D vitamin levels above 30 ng/mL, especially in winter [ 35 ]. The upper limit of supplementation for pregnant women is reported to be 5000 IU/day in the literature [ 46 ]. In our study population, the majority of the patients were not on vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, the Endocrine Society recommended 1000-4000 IU/day (up to 10.000 IU/day particularly for obese individuals) vitamin D supplementation to reach serum 25-OH D vitamin levels above 30 ng/mL, especially in winter [ 35 ]. The upper limit of supplementation for pregnant women is reported to be 5000 IU/day in the literature [ 46 ]. In our study population, the majority of the patients were not on vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Effective study doses of vitamin D were most often in the range of 400-2,000 IU (10-50 mcg), with the higher doses being given to adults (104). A 2020 study of pregnant women also found that daily supplementation is superior to boluses, that 2,000 IU/day was sufficient to resolve deficiency over time, and that up to 5,000 IU/day is safe (111).…”
Section: Controversy Over Recommended Supplement Dosesmentioning
confidence: 99%
“…Noting the overall divergence in populations studied, baseline Vitamin D levels and therapeutic Vitamin D doses used in the studies included in/excluded from various reviews, we consider the following conclusion from Corcoy et al ( 68 ) as a balanced summary: “High dose vitamin D supplementation during pregnancy halves the rate of GDM in pregnant women with baseline Vitamin D < 50 nmol/L”. Toxicity from Vitamin D supplementation up to 5,000 IU/day appears low ( 69 , 70 ). Therefore, in practical terms, Vitamin D therefore appears to be a reasonable option in populations with low baseline levels.…”
Section: Vitamin Dmentioning
confidence: 99%